The Influence Of Celebrity Endorser And Word Of Mouth On Oppo Smartphone Purchase Decision With Brand Image As An Intervening Variabel - Rossy, Asri Aneltha; Violinda, Qristin; Setyorini, Noni (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this research is to find out the influence of celebrity endorsers and word of mouth on the purchase decision of Oppo smartphones with brand image as mediation. Sampling was done using simple random sampling. The measurement scale uses the Likert scale. The data analysis uses validity, reliability, and hypothesis tests, with Partial Least Square processed using the outer model and inner model. The results of the study show that brand image has an effect on purchase decisions, celebrity endorsers have no effect on purchase decisions, word of mouth has an effect on purchase decisions, celebrity endorsers have an effect on brand image, word of mouth has an effect on brand image, and brand image It can mediate the celebrity endorser variable to the purchase decision, while the brand image cannot mediate the word of mouth variable to the purchase decision.